Sex-Specific Cut-Offs for High-Sensitivity Cardiac Troponin: Is Less More?. (5th February 2019) - Romiti, Giulio Francesco; Cangemi, Roberto; Toriello, Filippo; Ruscio, Eleonora; Sciomer, Susanna; Moscucci, Federica; Vincenti, Marianna; Crescioli, Clara; Proietti, Marco; Basili, Stefania; Raparelli, Valeria
Abstract : Management of patients presenting to the Emergency Department with chest pain is continuously evolving. In the setting of acute coronary syndrome, the availability of high-sensitivity cardiac troponin assays (hs-cTn) has allowed for the development of algorithms aimed at rapidly assessing the risk of an ongoing myocardial infarction. However, concerns were raised about the massive application of such a simplified approach to heterogeneous real-world populations. As a result, there is a potential risk of underdiagnosis in several clusters of patients, including women, for whom a lower threshold for hs-cTn was suggested to be more appropriate. Implementation in clinical practice of sex-tailored cut-off values for hs-cTn represents a hot topic due to the need to reduce inequality and improve diagnostic performance in females. The aim of this review is to summarize current evidence on sex-specific cut-off values of hs-cTn and their application and usefulness in clinical practice. We also offer an extensive overview of thresholds reported in literature and of the mechanisms underlying such differences among sexes, suggesting possible explanations about debated issues.